Which treatment strategy is preferred in the octogenarians with acute coronary syndrome? - Aydin, Gulay; Golcuk, Ebru; Bahat, Gulistan (Journal of the Pakistan Medical Association, 2023)
Objective: To compare the efficacy of invasive and conservative strategy in the management of octogenarians with acute coronary syndrome. Methods: The retrospective study was conducted after approval from the ethics review committee of University of Health Sciences, Derince Training and Research Hospital, Turkey and comprised data from April 2020 to April 2021 related to octogenarian patients of either gender admitted to University of Health Sciences, Darica Farabi Training and Research Hospital, Turkey with acute coronary syndrome diagnosis. The data was divided into invasive group A and conservative group B. Data was analysed using SPSS 25. Results: Of the 168 patients with median age 84(interquartile range: 81-86 years), there were 25(14.9%) in group A; 14(56%) males and 11(44%) females. There were 143(85.1%) patients in group B; 70(49%) males and 73(51%) females. Overall mortality was 111(66.1%); 11(44%) in group A, and 100(69.9%) in group B (p=0.012). Elevated alanine aminotransferase and invasive strategy were independent factors associated with mortality (p<0.05). Conclusion: The invasive strategy in the management of octogenarian patients presenting with acute coronary syndrome was found to be more efficient compared to the conservative strategy. Key Words: Octogenarians, Acute coronary syndrome, Mortality.